2016
DOI: 10.1128/mbio.00852-16
|View full text |Cite
|
Sign up to set email alerts
|

Erratum for Richmond et al., The Acinetobacter baumannii Two-Component System AdeRS Regulates Genes Required for Multidrug Efflux, Biofilm Formation, and Virulence in a Strain-Specific Manner

Abstract: V olume 7, no. 2, doi:10.1128olume 7, no. 2, doi:10. /mBio.00430-16, 2016. After careful review, it has come to our attention that the text in the abstract of our paper is at variance with one sentence in the article. During writing, revision, and editing, the sense was changed. The revised abstract below shows the correct text. We thank Maria Ramirez for bringing this to our attention.The opportunistic pathogen Acinetobacter baumannii is able to persist in the environment and is often multidrug resistant (MDR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…2527 These results are consistent with our phenotypic identification of MDROs using classical culture-dependent microbiological methods, and they highlight the potential to identify metabolic pathways and their byproducts as potential biomarkers of MDRO colonization, which may be widely applicable considering the functional stability of the human microbiome. 28 A recent study by Zhernakova et al 29 showed that the protein chromogranin A, retrieved from the stool, had a strong negative correlation with microbial diversity in the gut, suggesting that this fecal biomarker could be used to ascertain gut health.…”
Section: Discussionsupporting
confidence: 84%
“…2527 These results are consistent with our phenotypic identification of MDROs using classical culture-dependent microbiological methods, and they highlight the potential to identify metabolic pathways and their byproducts as potential biomarkers of MDRO colonization, which may be widely applicable considering the functional stability of the human microbiome. 28 A recent study by Zhernakova et al 29 showed that the protein chromogranin A, retrieved from the stool, had a strong negative correlation with microbial diversity in the gut, suggesting that this fecal biomarker could be used to ascertain gut health.…”
Section: Discussionsupporting
confidence: 84%
“…The response regulator component AdeR activates adeABC expression by binding to a direct-repeat motif in the intercistronic region 114 , and mutations in AdeR lead to enhanced efflux activity of AdeB 115 . AdeRS not only regulates the expression of the tripartite pump system encoded by adeABC, but also genes for biofilm formation and virulence 116 . Interestingly, TCSs can regulate more than one type of pump, such is the case of BaeSR in A. baumannii, which is proposed to indirectly regulate AdeAB and AdeIJK RND efflux pumps and also the MacAB ABC pump, and which has been suggested to influence increase resistance to tigecycline.…”
Section: [H1] Drug Efflux Pump Regulationmentioning
confidence: 99%
“…Within AdeRS, the histidine kinase AdeS senses environmental stimuli, while the response regulator AdeR mediates the cellular response by receiving a phosphoryl signal from AdeS and further stimulates the expression of its target genes ( 15 , 17 , 18 ). It is not only the production of the AdeABC efflux pump that is mediated; it is proposed that AdeRS also regulates genes required for biofilm formation and virulence, but in a strain-specific manner ( 19 ). Therefore, two-component systems have been highlighted to potentially serve as an effective drug target, especially by targeting the response regulator ( 16 , 20 ).…”
Section: Introductionmentioning
confidence: 99%